Socio-demographic factors and quality of life of head and neck cancer patients before and after treatment in the East Coast of Malaysia - Mohamed Ludin, Salizar; Che Abdullah, Che Azunie; Abdullah, Kahairi (IIUM Press, 2018)
Objective: This study aimed to determine the association of socio-demographic factors and quality of life (QOL) of HNC survivors before and after treatment in Malaysia. Methods: 40 HNC patients were recruited, and assessed for their with QOL with Life Cancer Survivor (QLQ-CS) Head & Neck 35 (QLQ-H&N35) questionnaire pre-treatment and six months post-treatment. One way analysis of variance (ANOVA) and paired t-test were done to analyse the data. Results: The result shows that the QOL of HNC patients were at medium level (total mean score M= 6.22) before treatment, and reduced (total mean score M= 4.84) at 6 months after treatment) . Only health history was seen significantly associated with QOL of HNC patients, both pre and post-treatment. Post treatment showed only marital status factor associated with QOL of HNC patients. The paired sample t-test result shows that the symptoms /problem pre- treatment (M = 255.10, SD = 20.405 )was lower than post treatment (M = 201.80, SD = 22.025)(t (49) = 9.337; p =0.001). Conclusions: The present research suggested that the patients’ QOL is reduced after treatment (medium level). This could be due to the advancement of the cancer and evidence when the health history and symptoms found significantly associated with the QOL. Thus, socio-demographic factors is very crucial factors that must be considered during patients’ assessment in improving patients’ care and optimum QOL pre and post treatment.